Telocytes in regenerative medicine - Bei, Yihua (J Cell Mol Med, 2015)
Telocytes (TCs) are a distinct type of interstitial cells characterized by a small cell body and extremely long and thin telopodes (Tps). The presence of TCs has been documented in many tissues and organs (go to http://www.telocytes.com). Functionally, TCs form a three-dimensional (3D) interstitial network by homocellular and heterocellular communication and are involved in the maintenance of tissue homeostasis. As important interstitial cells to guide or nurse putative stem and progenitor cells in stem cell niches in a spectrum of tissues and organs, TCs contribute to tissue repair and regeneration. This review focuses on the latest progresses regarding TCs in the repair and regeneration of different tissues and organs, including heart, lung, skeletal muscle, skin, meninges and choroid plexus, eye, liver, uterus and urinary system. By targeting TCs alone or in tandem with stem cells, we might promote regeneration and prevent the evolution to irreversible tissue damage. Exploring pharmacological or non-pharmacological methods to enhance the growth of TCs would be a novel therapeutic strategy besides exogenous transplantation for many diseased disorders.